2009
DOI: 10.1002/cncr.24620
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous computed tomography‐guided lung biopsy and pleural dissemination

Abstract: Objective Connective tissue growth factor (CTGF; CCN2) is overexpressed in systemic sclerosis (SSc) and has been hypothesized to be a key mediator of the pulmonary fibrosis frequently observed in this disease. CTGF is induced by transforming growth factor β (TGFβ) and is a mediator of some profibrotic effects of TGFβ in vitro. This study was undertaken to investigate the role of CTGF in enhanced expression of type I collagen in bleomycin‐induced lung fibrosis, and to delineate the mechanisms of action underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…However, there is some concern that biopsy may result in tumor seeding and possibly contribute to recurrences. At least in the surgery literature, the evidence seems to support no needle dissemination from CT-guided lung biopsies(33). Moreover, the overall rate of local recurrence in our cohort of biopsied patients was similar to published rates including studies where not all patients were biopsied.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some concern that biopsy may result in tumor seeding and possibly contribute to recurrences. At least in the surgery literature, the evidence seems to support no needle dissemination from CT-guided lung biopsies(33). Moreover, the overall rate of local recurrence in our cohort of biopsied patients was similar to published rates including studies where not all patients were biopsied.…”
Section: Discussionmentioning
confidence: 99%
“…Sano et al 29 have attempted to address this concern with a prospective study. They performed intraoperative pleural lavage on 412 patients undergoing resection of a lung cancer, 171 of whom had undergone transthoracic needle biopsy prior to surgery.…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 13 , 15 However, Sano et al reported that preoperative percutaneous CT-guided needle biopsy did not lead to pleural dissemination, as determined by intraoperative pleural lavage cytology in patients with lung cancer. 27 Recent studies also demonstrated that PNB was not associated with increased pleural recurrence or impaired survival outcomes in NSCLC patients. 14 , 16 , 28 Importantly, a recent meta-analysis, including these related observational studies revealed that PNB did not increase the risk of pleural recurrence compared with non-percutaneous transthoracic needle biopsy strategies in early-stage lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%